A direct FeCl3-catalyzed cross-coupling and cyclization reactions: A new approach to the construction of functionalized pyrano[3, 2-a]carbazole derivatives. Issue 32 (10th August 2017) - Tan, Siow-Ping; Ahmad, Kartini; Nafiah, Mohd Azlan
Abstract: The FeCl3 -catalyzed cross-coupling through a sequential C−N and C−C bond-forming via tandem C−H and N−H bonds functionalization represents a novel method for the formation of dimeric carbazole derivatives. This approach provides a novel dimeric carbazole, namely murrabicine (4 ), from murrayacine (1 ). Following the same procedure, a cycloadduct (6 ) has been achieved due to different substitution pattern at the pyran ring of the mahanimbine (3 ). This strategy opens up an efficient and direct route to the formation of biologically important pyrano[3, 2- a ]carbazole alkaloids. Graphical abstract: